Modification and Perfomance Test of Orbapas (Soybean Seed Peeler) - Lutfi, Musthofa; Fanani, Ahmad; Abdul Fatah, Gatot Suharto (Fakultas Teknologi Pertanian Universitas Brawijaya, 2010)
The objective of this research is modification of driving engine on soybean seed peeler Orbapas uses an electric motor, and then examination the performance of modified Orbapas. The hypothesis of this study is the greater the speed of rotation Orbapas, will result the greater peeling capacity. The research was done by modification of peeler with add electric motor, gearbox, and holder, then the performance of peeler with 3 speed was tested. Result of this research showed that the peeling capacity increased after modification of Orbapas as followed:15.67 kg/hour at 73 rpm, 19.46 kg/hour at 93 rpm, and 21.9 kg/hour at 119 rpm, compared to original capacity of 14.12 kg/hour at 80 rpm.Keywords: orbapas, peeling capacity, electric motor